Sustainability criteria for assessing nanotechnology applicability in industrial wastewater treatment: Current status and future outlook. (April 2019) - Kamali, Mohammadreza; Persson, Kenneth M.; Costa, Maria Elisabete; Capela, Isabel
Abstract: Application of engineered nanomaterials for the treatment of industrial effluents and to deal with recalcitrant pollutants has been noticeably promoted in recent years. Laboratory, pilot and full-scale studies emphasize the potential of this technology to offer promising treatment options to meet the future needs for clean water resources and to comply with stringent environmental regulations. The technology is now in the stage of being transferred to the real applications. Therefore, the assessment of its performance according to sustainability criteria and their incorporation into the decision-making process is a key task to ensure that long term benefits are achieved from the nano-treatment technologies. In this study, the importance of sustainability criteria for the conventional and novel technologies for the treatment of industrial effluents was determined in a general approach assisted by a fuzzy-Delphi method. The criteria were categorized in technical, economic, environmental and social branches and the current situation of the nanotechnology regarding the criteria was critically discussed. The results indicate that the efficiency and safety are the most important parameters to make sustainable choices for the treatment of industrial effluents. Also, in addition to the need for scaling-up the nanotechnology in various stages, the study on their environmental footprint must continue in deeper scales under expected environmental conditions, in particular the synthesis of engineered nanomaterials and the development of reactors with the ability of recovery and reuse the nanomaterials. This paper will aid to select the most sustainable types of nanomaterials for the real applications and to guide the future studies in this field. Highlights: Sustainability criteria for industrial wastewater treatments are investigated. Nanomaterials application for the treatment of industrial effluents is assessed. Opportunities for industrial wastewater treatment with nanomaterials are discussed.